Analisis Faktor yang Mempengaruhi Auditor Switching pada perusahaan Manufaktur - Rehania Wardani (Universitas Sarjanawiyata Tamansiswa, 2019)
The study analyzed the influence of the audit opinion, change of management, size of the company, and the percentage of ROA's change to auditors switching to manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. Sampling is done by purposive sampling, resulting in a total sample of 65 company observations. Methods of data analysis using logistic regression analysis. The results showed that only change management variables had an influence on the auditor switching, while the audit opinion variables, company size, and ROA change percentages had no effect on auditor switching. Keywords: opinio, change of management, company size, ROA, auditor switching